2016
DOI: 10.5539/ies.v9n7p135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bilateral Effects between Social Undermining and Co-Creation among University Faculty Members

Abstract: Understanding the social undermining is increasing important in organizational literature both because of its relation with job performance and because of its collective cost to individuals and organizations. This article argued that social undermining can effect on co-creation among faculty members. The study adopted a descriptive-correlational method. The statistical population of the study consisted university faculty members in Iran, that 235 members were selected as the participants using stratified rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…More specifically, the teaching faculty of universities showed that emotional support from coworkers will help them to increase their wellbeing at the workplace. The indirect effect of emotional support and welling was tested in presence of social undermining which one of the vital aspects in an organizational is setting (Taherpour et al, 2016). It is concluded that the well-being of the employees can be improved by reducing the negative behaviors among the employees at the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More specifically, the teaching faculty of universities showed that emotional support from coworkers will help them to increase their wellbeing at the workplace. The indirect effect of emotional support and welling was tested in presence of social undermining which one of the vital aspects in an organizational is setting (Taherpour et al, 2016). It is concluded that the well-being of the employees can be improved by reducing the negative behaviors among the employees at the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Negative personal effects such as sadness, low self-esteem, and psychosomatic problems might result from these practices (Duffy et al, 2006). As a result, social undermining can have negative impact on interpersonal connections and co-creation in the workplace (Taherpour et al, 2016). Joseph et al (2011) reported that social undermining behavior is employed in the workplace to prevent coworkers from establishing and maintaining a good reputation, achievement, and healthy interpersonal relationships.…”
Section: Social Undermining and Wellbeingmentioning
confidence: 99%
See 3 more Smart Citations